Evaluation of occupants’ satisfaction with on-campus private hostel in a Nigerian university - Olukolajo, Michael Ayodele; Mbazor, David (Penerbit Universiti Kebangsaan Malaysia, 2021)
The study evaluated the satisfaction of occupants of a private female hostel (Federal University of Technology Akure Academic Staff Cooperative Society - FUTAASCOOPS hostel) located at the Federal University of Technology Akure, Nigeria in terms of its structural components, accommodation provided, services/amenities, locational attributes and the environment. The hostel being a private investment is not wholly under the direct control and management of the University. Primary data was collected from the occupants of the hostel through 85 questionnaires distributed to them following a random sampling technique. A total of 70 questionnaires representing 82.4% of the population were retrieved and found valid for the analysis. Data analysis was conducted using percentage frequency distribution table, Weighted Mean Score (WMS) and Relative Satisfaction Index (RSI). Findings revealed that respondents consider the structural element, environment and locational attributes of the hostel satisfactory. The bedrooms, lobby, bathrooms, and kitchen except common room and laundry among the accommodation details were also considered satisfactory. Services/amenities provided in the hostel were generally unsatisfactory to the respondents. The study recommends that the investor, through sound management approach should sustain the satisfaction derived by the occupants, and improve the standard of amenities in the hostel to sustain patronage and prevent possible loss of value.